AIDS up to the Year 2000 - Boom, F. M. L. G. van den; Jager, J. C.; Reinking, D. P.; Postma, M. J. (Future Health Scenarios, 1992)
In March 1983 the Secretary of State for Welfare, Health and Cultural Affairs appointed the Steering Committee on Future Health Scenarios (STG). The task of the STG is to advise the Minister on the future of public health and health care in the long term in the Netherlands with a view to increasing the anticipatory capacity of government policy. Since 1983 the STG has set up a number of committees, including the Scenario Committee on AIDS, with a view to mapping out possible scenarios in their particular field of interest. The committees report in the form of scenario reports, which are of relevance not just to the national government but also to others involved in policy development and opinion formation in the field in question.